2020
DOI: 10.1111/pai.13420
|View full text |Cite
|
Sign up to set email alerts
|

Novel SERPING1 gene mutations and clinical experience of type 1 hereditary angioedema from North India

Abstract: Background: There is paucity of literature on long-term follow-up of patients with hereditary angioedema (HAE) from developing countries. Objective: This study was carried out to analyze the clinical manifestations, laboratory features, and genetic profile of 32 patients (21 male and 11 female) from 23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…There are several reasons for these shortfalls: Our experience with SERPING1 gene sequencing in patients with type 1 HAE at PGIMER in Chandigarh (India) has shown 9 novel (likely pathogenic) and 2 previously reported diseasecausing variants in 11 families where a SERPING1 variant could be detected. No disease-causing variants in SERPING1 gene were detected in 9 other suspected families tested [9]. Thus, in our practice, genetic diagnosis failed to diagnose 9/20 (diagnostic sensitivity of 45%) of those with biochemically proven quantitative C1-INH deficiency, while incautious interpretation of variants of unknown significance might risk false positives, reducing specificity of the test.…”
Section: Diagnosismentioning
confidence: 68%
See 4 more Smart Citations
“…There are several reasons for these shortfalls: Our experience with SERPING1 gene sequencing in patients with type 1 HAE at PGIMER in Chandigarh (India) has shown 9 novel (likely pathogenic) and 2 previously reported diseasecausing variants in 11 families where a SERPING1 variant could be detected. No disease-causing variants in SERPING1 gene were detected in 9 other suspected families tested [9]. Thus, in our practice, genetic diagnosis failed to diagnose 9/20 (diagnostic sensitivity of 45%) of those with biochemically proven quantitative C1-INH deficiency, while incautious interpretation of variants of unknown significance might risk false positives, reducing specificity of the test.…”
Section: Diagnosismentioning
confidence: 68%
“…Thus, India illustrates the unfortunate and disparate situation seen for HAE patients in many low-income countries compared with higher-income countries. It has been reported that delays in diagnosis of HAE are very common in India, with a median delay in diagnosis of 6.5 years (range 0-28 years) [9]. Of note, it is very typical for parents or grandparents not to receive their initial diagnosis of HAE until their children or grandchildren begin to have symptoms [9].…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations